1994
DOI: 10.1104/pp.104.2.769
|View full text |Cite
|
Sign up to set email alerts
|

Mutants of Chloroplast Coupling Factor Reduction in Arabidopsis

Abstract: We have devised a two-step screening strategy for the selection of chloroplast coupling factor reduction mutants from an Mz population of Arabidopsis fhaliana. The selection strategy relies on a lowered energetic threshold for catalytic activation of the enzyme that has been shown to accompany thioredoxin-mediated reduction of a cysteine bridge on the y subunit of coupling factor. W e selected first for plants that grew poorly under low irradiance but performed satisfactorily at high irradiance when the transm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
23
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 18 publications
4
23
0
Order By: Relevance
“…The slow first-order decay of ⌬A 518 (time constant of ⌬A 518 decay () ϭ 257 ms) in dark-adapted wild-type leaves (Fig. 1A, D ad trace) indicated that the catalytically inactive form of the ATP synthase predominated (20) and that the decay was due mainly to slow depolarization by ion movement across the thylakoid membrane rather than proton efflux through the ATP synthase. In wild-type leaves, 7 s of pre-illumination with 65 mol m Ϫ2 s Ϫ1 red light was sufficient to fully activate the ATP synthase and to bring about the thioredoxin-dependent reduc- tion of the ␥-subunit.…”
Section: Light-dependent Reduction Of the Chloroplast Atp Synthasementioning
confidence: 99%
See 2 more Smart Citations
“…The slow first-order decay of ⌬A 518 (time constant of ⌬A 518 decay () ϭ 257 ms) in dark-adapted wild-type leaves (Fig. 1A, D ad trace) indicated that the catalytically inactive form of the ATP synthase predominated (20) and that the decay was due mainly to slow depolarization by ion movement across the thylakoid membrane rather than proton efflux through the ATP synthase. In wild-type leaves, 7 s of pre-illumination with 65 mol m Ϫ2 s Ϫ1 red light was sufficient to fully activate the ATP synthase and to bring about the thioredoxin-dependent reduc- tion of the ␥-subunit.…”
Section: Light-dependent Reduction Of the Chloroplast Atp Synthasementioning
confidence: 99%
“…Measurement of ⌬A 518 Relaxation Kinetics-Plants ϳ45 days old were initially dark-adapted for 12 h to ensure that ␥-subunits of ATP synthase within the leaves were fully oxidized. A kinetic spectrophotometer was used to monitor the flash-induced absorbance change at 518 nm with detached leaves as described previously (20) with the exception that 7 s of continuous red light (65 mol m Ϫ2 s…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We conclude that these acidic residues are important for adjusting thiol redox properties. In another Arabidopsis mutant, cfq (18,35), a single substitution of another highly conserved glutamate group (E244K) in the ␥ subunit resulted in more negative redox potential, rendering the complex more prone to oxidation in the dark. Deletion or mutation of the negatively charged residues Glu 210 -Asp 211 -Glu 212 in this region in the thermophilic bacterium Bacillus PS3 (30,31,36) resulted in reverse redox sensitivity, i.e.…”
Section: Atp Synthase In Mothra Is Equally Active In the Light-andmentioning
confidence: 99%
“…This property has been used to identify coupling factor reduction mutants in Arabidopsis which grow poorly in dim light and showed slowed ⌬A 518 decay after light-dark transition (22). One coupling factor quick recovery mutant, cfq, contains an E244D point mutation in the ␥ subunit leading to a decreased acidification of the lumen compared with wild type in the initial few minutes of the induction period under subsaturating light conditions.…”
mentioning
confidence: 99%